2021
DOI: 10.2147/nss.s305850
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive and Central Sleep Apnea in First Ever Ischemic Stroke are Associated with Different Time Course and Autonomic Activation

Abstract: Introduction: Sleep-related breathing disorders are highly prevalent in patients with ischemic stroke. Among sleep-disordered breathing disorders, obstructive sleep apnea is the most represented one, but central sleep apnea, isolated or in the context of a periodic breathing/Cheyne-Stokes respiration, is frequently reported in these patients. Altered baroreflex responses have been reported in the acute phases of a cerebral event. Methods: We conducted, in a group of patients with ischemic stroke (n=60), a pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Notably, we excluded central apneas and hypopneas from the count of O-AHI. We excluded central events because of the well-documented relatively high prevalence of central apneas in both AF and acute stroke [ 16 , 17 ]. Additionally, central apneas recognize a different pathogenic mechanism compared to obstructive apneas [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we excluded central apneas and hypopneas from the count of O-AHI. We excluded central events because of the well-documented relatively high prevalence of central apneas in both AF and acute stroke [ 16 , 17 ]. Additionally, central apneas recognize a different pathogenic mechanism compared to obstructive apneas [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the pathogenic pathways behind OSA and CSA are different, future studies should count separately the AHI of central and obstructive events and consider a mixed respiratory pattern when these two conditions coexist. In fact, studies that took into the account a mixed pattern, characterized by the coexistence of central and obstructive events, observed a high proportion of such pattern in both acute [41] and chronic phases [42•].…”
Section: Sleep Apnea In Stroke Patients: New Onset or Pre-existing Co...mentioning
confidence: 99%
“…Moderate-to-severe OSA is more frequent in wake-up strokes compared to non-wake up strokes [5]. A recent study observed a high prevalence and variability of Sleep-disordered breathing in the acute phase of cerebral ischemic events [6]. However, the correlation between OSAHS and cerebrovascular disease has not been studied extensively and a lot of queries remain unanswered, such as, the pathophysiological mechanism that links them.…”
Section: Introductionmentioning
confidence: 99%